Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.46586/tosc.v2017.i4.130-168
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Implementations of Lightweight Building Blocks

Abstract: We study the synthesis of small functions used as building blocks in lightweight cryptographic designs in terms of hardware implementations. This phase most notably appears during the ASIC implementation of cryptographic primitives. The quality of this step directly affects the output circuit, and while general tools exist to carry out this task, most of them belong to proprietary software suites and apply heuristics to any size of functions. In this work, we focus on small functions (4- and 8-bit mappings) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Definition 4. [JPST17] [Sequential XOR count (s-XOR)] Given a non-singular matrix M ∈ GL(n, F 2 ) of order n over F 2 , the sequential XOR count or s-XOR of M , denoted by C s (M ), is the smallest integer t such that the matrix M can be decomposed as…”
Section: Mds Matrices and The Cost Of Their Hardware Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Definition 4. [JPST17] [Sequential XOR count (s-XOR)] Given a non-singular matrix M ∈ GL(n, F 2 ) of order n over F 2 , the sequential XOR count or s-XOR of M , denoted by C s (M ), is the smallest integer t such that the matrix M can be decomposed as…”
Section: Mds Matrices and The Cost Of Their Hardware Implementationmentioning
confidence: 99%
“…It was also shown that the optimal implementation of an MDS matrix depends upon the minimum number of additive elementary matrices (known as Type III) that appear in its decomposition. It was then reformulated in [JPST17,BKL16] as sequential XOR or s-XOR to estimate the implementation cost. Also, a graph-based meet-in-the-middle (MITM) search algorithm to find efficient implementation of MDS matrices called LIGHTER was developed in [JPST17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [13], authors presented the 4-bit Sbox implementation generator for quantum computers, namely LIGHTER-R. LIGHTER-R is an extension of LIGHTER developed for classical computers, targeting quantum computers [16]. The LIGHTER uses the Meet In The Middle approach to design the compact result of 4-bit Sbox for classical computers.…”
Section: Lighter-rmentioning
confidence: 99%
“…In addition to construction methods described for MDS matrices, recently, MDS construction methods have evolved to find MDS matrices with minimal XOR counts [21], which is a metric used in the estimation of hardware implementation cost. In the literature, some studies focusing on generating MDS matrices with low/minimum XOR counts are given in [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%